2008
DOI: 10.1200/jco.2008.26.15_suppl.16020
|View full text |Cite
|
Sign up to set email alerts
|

Phase I study combining treatment with temsirolimus and sunitinib malate in patients with advanced renal cell carcinoma

Abstract: Purpose-Concurrent inhibition of multiple oncogenic signaling pathways might improve the efficacy of anticancer agents and abrogate resistance mechanisms. This phase I study evaluated temsirolimus in combination with sunitinib in patients with advanced RCC.Patients and Methods-Eligibility included advanced RCC and ≤ 2 previous systemic regimens. At the starting dose, temsirolimus 15 mg was administered by intravenous (I.V.) infusion once weekly, and sunitinib 25 mg was administered orally once daily for 4 week… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 10 publications
0
19
0
Order By: Relevance
“…In a phase I trial in patients with previously treated advanced RCC, VEGFR tyrosine kinase inhibition with sunitinib plus downstream mTOR inhibition with temsirolimus resulted in substantial toxicity at low starting doses of both agents (sunitinib, 25 mg daily; temsirolimus, 15 mg once weekly), causing trial termination [38].…”
Section: Sunitinib Combinationsmentioning
confidence: 99%
“…In a phase I trial in patients with previously treated advanced RCC, VEGFR tyrosine kinase inhibition with sunitinib plus downstream mTOR inhibition with temsirolimus resulted in substantial toxicity at low starting doses of both agents (sunitinib, 25 mg daily; temsirolimus, 15 mg once weekly), causing trial termination [38].…”
Section: Sunitinib Combinationsmentioning
confidence: 99%
“…Sometimes drug combinations will be abandoned if the combined toxicity requires such extensive dose reductions that the actual administered doses may be ineffective (e.g., sunitinib and temsirolimus; ref. 25). When combinations of drugs must be administered at a substantially lower dose than planned because of toxicity, it is often unclear whether the lower dose would truly be too low to show efficacy, as such dose reductions typically result in the abandonment of further efficacy analyses.…”
Section: Clinical Trials Of Combinationsmentioning
confidence: 99%
“…Feldman et al [29], Sosman et al [30], Fischer et al [31] Combination therapy Excess toxicity observed with combinations of sunitinib + bevacizumab or sunitinib + temsirolimus Sorafenib + bevacizumab combination seems promising…”
Section: Optimizing the Use Of Approved Agentsmentioning
confidence: 98%
“…Similarly, the combination of sorafenib and bevacizumab produced an impressive response rate of 52% in a phase 1 trial; however, bevacizumab appeared to increase known sorafenib-associated toxicities (hand-foot syndrome, anorexia, hypertension, fatigue), and the maximal tolerated dose was 200 mg by mouth daily (one fourth of the full dose) for sorafenib and 5 mg/kg intravenously every 2 weeks (half the full dose) for bevacizumab [30]. Furthermore, a phase 1 trial of the combination of sunitinib and temsirolimus was terminated after only three patients were accrued because of substantial toxicity observed at low starting doses of both agents [31].…”
Section: Optimizing Patient Selectionmentioning
confidence: 99%